ЛЕЧЕНИЕ ГАСТРОЭЗОФАГЕАЛЬНОЙ РЕФЛЮКСНОЙ БОЛЕЗНИ КОМБИНИРОВАННЫМ ПРЕПАРАТОМ «ДОМСТАЛ-О» («Наука и здравоохранение», 2026)
ЛЕЧЕНИЕ ГАСТРОЭЗОФАГЕАЛЬНОЙ РЕФЛЮКСНОЙ БОЛЕЗНИ КОМБИНИРОВАННЫМ ПРЕПАРАТОМ «ДОМСТАЛ-О»